2021
DOI: 10.1017/s0007114521003706
|View full text |Cite
|
Sign up to set email alerts
|

Could consumption of yam (Dioscorea) or its extract be beneficial in controlling glycaemia: a systematic review

Abstract: Yam (Dioscorea spp.) and its associated extracts have been shown to possess a variety of biological activities and identified as beneficial in the control of glycaemia in patients with Type II Diabetes Mellitus (T2DM). The objective was to conduct a systematic search of the literature to investigate whether yam and its extract can improve glycaemia and whether consumption of yam could be beneficial for managing T2DM. Using the PRISMA guidelines and the PICO framework, three databases (PubMed, Scopus, and Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Its quality is excellent and it has high medicinal value 2 . Studies have confirmed that yams have the effect of lowering blood sugar, lowering blood fat, and strengthening immunity 3,4 . Based on this, how to improve the effective value of Chinese yam has become a hot topic in recent years.…”
Section: Introductionmentioning
confidence: 95%
“…Its quality is excellent and it has high medicinal value 2 . Studies have confirmed that yams have the effect of lowering blood sugar, lowering blood fat, and strengthening immunity 3,4 . Based on this, how to improve the effective value of Chinese yam has become a hot topic in recent years.…”
Section: Introductionmentioning
confidence: 95%
“…However, apart from its nutritional value, DP has great pharmaceutical potential, as it has been used for centuries in Traditional Chinese Medicine (TCM) [ 3 ]. Its pharmacological effects are manifold, with a particular focus on the improvement of glycemia in patients suffering from diabetes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…People progressively recognize the harm of the high-fat diet (HFD) and the importance of a scientific diet, therefore they focus on enhancing bodily function through the use of functional foods (4,5). Currently, Chinese herbs such as Panax ginseng, Panax notoginseng, and Chinese yam have been experimentally validated for reducing the risk of cardiovascular disease in animal studies (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%